2008
DOI: 10.1073/pnas.0710311105
|View full text |Cite
|
Sign up to set email alerts
|

Force-generation and dynamic instability of microtubule bundles

Abstract: Individual dynamic microtubules can generate pushing or pulling forces when their growing or shrinking ends are in contact with cellular objects such as the cortex or chromosomes. These microtubules can operate in parallel bundles, for example when interacting with mitotic chromosomes. Here, we investigate the forcegenerating capabilities of a bundle of growing microtubules and study the effect that force has on the cooperative dynamics of such a bundle. We used an optical tweezers setup to study microtubule b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

15
140
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(155 citation statements)
references
References 37 publications
15
140
0
Order By: Relevance
“…Individual MTs are "dynamically unstable," spontaneously switching between a polymerizing state and a depolymerizing state (1) with growth, shortening, and switching rates that are regulated by the forces exerted at the MT tips (2)(3)(4)(5)(6). For many eukaryotes, however, multiple MTs are connected to each kinetochore, giving rise to collective MT behavior that is not well understood and can be entirely different from the behavior of individual MTs.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Individual MTs are "dynamically unstable," spontaneously switching between a polymerizing state and a depolymerizing state (1) with growth, shortening, and switching rates that are regulated by the forces exerted at the MT tips (2)(3)(4)(5)(6). For many eukaryotes, however, multiple MTs are connected to each kinetochore, giving rise to collective MT behavior that is not well understood and can be entirely different from the behavior of individual MTs.…”
mentioning
confidence: 99%
“…Another model proposes that oscillations occur via a general mechanobiochemical feedback (25). Models of force-dependent MTs interacting with the same object also exhibit cooperative behavior (5,(26)(27)(28)(29). However, these models do not explain error correction dynamics.…”
mentioning
confidence: 99%
“…On the other hand, in similar experiments performed on microtubules, researchers have found that the growth velocity of the filament growing against an immobile barrier decreases with increased resistance -from 1.2µm per minute at zero load to 0.2µm per minute at 4pN to 5pN force, which is the putative stall force in this case [39]. In another experiment based on microtubules, using optical tweezers, Laan et al [42] report that stall forces of 2.7pN, 5.5pN and 8.1pN are produced by groups of filaments. They in-terpreted this as containing one, two and three filaments, respectively.…”
Section: Introductionmentioning
confidence: 89%
“…To understand collective force generation by polymerizing biofilaments, researchers typically resort to in vitro experiments in which biofilaments are polymerised either in the form of bundles or branched sheets against a barrier, which resists their motion by producing reaction * These two authors contributed equally forces [36,[39][40][41][42][43]. One important focus of these studies is a quantity called the stall force, which is defined as the resisting force at which the mean growth velocity of the collection of filaments is zero, and is the maximum pushing force generated by these filaments.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation